Evaluation of sodium nitroprusside for controlled hypotension in children during surgery - Drover, David R.; Hammer, Gregory B.; Barrett, Jeffrey S.; Cohane, Carol A.; Reece, Tammy; Zajicek, Anne; Schulman, Scott (Frontiers in Pharmacology, 2015)
Purpose. (1) To define the onset and offset of the blood-pressure-lowering effects of sodium nitroprusside (SNP) for use in developing instructions for dose titration in children undergoing a surgical or medical procedure, and (2) to assess the safety of SNP administration in pediatric patients requiring controlled reduction of blood pressure. Methods. We conducted a randomized, double-blind, parallel-group, dose-ranging, effect-controlled, multicenter study of intravenous (IV) infusions of SNP in pediatric patients <17 years, who required controlled hypotension for at least 2 hours while undergoing a surgical or medical procedure. A blinded SNP dose of 0.3, 1, 2, or 3 µg/kg/min was infused for 30 min, followed by open-label administration for at least 90 min. Both infusions were titrated to effect. Results. The final intent-to-treat group comprised 203 patients. Significant reductions in mean arterial pressure (MAP) from baseline were observed for all four doses at 20 and 25 minutes after the start of infusion (p≤0.009 and p≤0.010 for each time, respectively). Overall, 98.5% of the patients achieved the target MAP; 72.9% first achieved the target MAP during the blinded infusion. The mean infusion rate at target MAP was 1.07 µg/kg/min. Conclusion. We determined that 0.3 µg/kg/m is a reasonable starting dose for SNP in pediatric patients requiring controlled hypotension. The infusion rate can then be increased to achieve the desired reduction in blood pressure. On the basis of our results, we found an average infusion rate of 1 µg/kg/min might be appropriate. Of note, no cyanide toxicity was reported, and no measureable cyanide levels were detected in any blood samples obtained during the study. http://clinicaltrials.gov/show/NCT00135668